Analysis on Human Resource Management and Conflict Resolution in The Long Road of Indonesian Era - Sri Sundari (Universitas Sultan Ageng Tirtayasa, 2022)
As a nation, Indonesia is still in the process of nation-building. Since the beginning of Indonesia's independence, youth or young groups have played a key role in the nation-building process that determines the direction of the next development of the Indonesian state. Young people, from time to time, have distinctive characteristics that are influenced by the socio-cultural-political conditions in which they grow up. The interactions that occur between young people and the government will have an impact on future leadership styles. This paper aims to describe the pattern of human resource management in Indonesia's nation-building process, particularly in analysing the pattern of conflict resolution between the youth and the government in each era of Indonesian leadership (Old Order, New Order, and Post-Reformation)